1991
DOI: 10.1111/j.1745-9125.1991.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

From Initial Deterrence to Longterm Escalation: Short‐custody Arrest for Poverty Ghetto Domestic Violence*

Abstract: and 35 Officers of the Milwaukee Police DepartmentPersons arrested for misdemeanor domestic violence are held in custody for wideb varying lengths of time. To test the eflects of this variance, we randomly assigned short (2 = 2.8 hours), full (f = 11.1 hours), and no arrests (warning only) to a sample of 1,200 cases with predominantly unemployed suspects concentrated in black ghetto poverty neighborhoods in Milwaukee. Victim interviews and one official measure showed that short arrest had a substantial initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 17 publications
2
53
3
Order By: Relevance
“…Also, and although the two had hypothesized significantly higher re-arrest likelihoods for lower stake offenders serving probation and/or jail (Wooldredge and Thistlehwaite 2002), they found the opposite to be true. Their findings stand in contradiction to at least three of the 1990s replication study group cities showing employed suspects tending to be deterred by arrest, while unemployed suspects tending to become more frequently violent following arrest (Dunford, Huizinga, and Elliott 1990;Sherman et al 1991). A number of studies (Berk et al 1992;Garner and Maxwell 1995;Sherman and Smith 1992;Sherman et al 1991) found arrest to be more effective for reducing the likelihood of re-arrest for intimate assault among misdemeanor domestic violence offenders with higher stakes in conformity.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Also, and although the two had hypothesized significantly higher re-arrest likelihoods for lower stake offenders serving probation and/or jail (Wooldredge and Thistlehwaite 2002), they found the opposite to be true. Their findings stand in contradiction to at least three of the 1990s replication study group cities showing employed suspects tending to be deterred by arrest, while unemployed suspects tending to become more frequently violent following arrest (Dunford, Huizinga, and Elliott 1990;Sherman et al 1991). A number of studies (Berk et al 1992;Garner and Maxwell 1995;Sherman and Smith 1992;Sherman et al 1991) found arrest to be more effective for reducing the likelihood of re-arrest for intimate assault among misdemeanor domestic violence offenders with higher stakes in conformity.…”
Section: Introductioncontrasting
confidence: 48%
“…Their findings stand in contradiction to at least three of the 1990s replication study group cities showing employed suspects tending to be deterred by arrest, while unemployed suspects tending to become more frequently violent following arrest (Dunford, Huizinga, and Elliott 1990;Sherman et al 1991). A number of studies (Berk et al 1992;Garner and Maxwell 1995;Sherman and Smith 1992;Sherman et al 1991) found arrest to be more effective for reducing the likelihood of re-arrest for intimate assault among misdemeanor domestic violence offenders with higher stakes in conformity. Interestingly, their examination of the conditioned effects of informal controls (i.e., residential stability levels, education level, economic status) as they increase "dosage" to stake in conformity shares, find consistency with both Berk et al (1992), and Sherman and Smith (1992) that legal sanctions are significantly more effective for deterring individuals who are committed to more conventional values (Wooldredge and Thistlehwaite 2002).…”
Section: Introductioncontrasting
confidence: 48%
“…One of the reasons for this lack of data is that cumulative exposure to IPV is difficult to measure. IPV is often recurrent and persistent; women may experience IPV from multiple partners over their lifecourses (Burgess et al, 1997;Sherman et al, 1991;Tjaden & Thoennes, 2000;Yoshihama & Gillespie, 2002). Several studies have found a strong positive association between the frequency and duration/chronicity of violence and the severity of psychological distress among battered women (Astin, Lawrence, & Foy, 1993;Gelles & Harrop, 1989;Kemp et al, 1991).…”
Section: Putting It All Together: An Ecological Lifecourse Approach Tmentioning
confidence: 99%
“…Their experiment has been recognized as one of the most important in criminology, because of the wide publicity of the finding that the arresting of offenders reduced repeat violence (Farrington and Welsh 2005). The National Institute of Justice funded multiple replications of the Minneapolis study, and many of these were also among the most cited policing experiments: Omaha Dunford 1990), Miami (Pate and Hamilton 1992), Milwaukee (Sherman et al 1991(Sherman et al , 1992, Charlotte (Hirschel et al 1992) and Colorado Springs (Berk et al 1992). Aside from the multitude of experiments covering domestic violence arrests, the list below includes frequently cited experimental assessments of police innovations such as problemoriented policing (Braga et al 1999;Weisburd and Green 1995) and hot spots policing (Sherman and Weisburd 1995).…”
Section: Resultsmentioning
confidence: 98%